The use of maggot (Hermetia illlucens) oil in artificial feeds on the growth performance and survival rate of saline tilapia (Oreochromis niloticus) - Seto Windarto; Hasbi Ash Shiddieqi; Slamet Budi Prayitno; Damang Suryanto; Sapto Purnomo Putro; Vivi Endar Herawati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Tilapia is one of the commodities favored by the community and is widely cultivated in Indonesia. At this time, the development of tilapia cultivation has entered the location of marine and brackish waters, known as saline tilapia. The increase in tilapia cultivation has increased feed production, so the price of raw materials, especially fish oil, has increased. The source of crude fat that is usually used in feed formulations is fish oil, but the availability of fish oil is limited, so the price is increasing. One of the alternatives that can replace fish oil is maggot oil. Maggot contains 42-48% lipids. The purpose of this study is to find the effect of giving maggot oil on the growth and survival of saline tilapia. The method used was experimental, with a completely randomized design (CRD) consisting of 4 treatments and three replications. The treatments tested were treatment A (control), B (1.5 ml of maggot oil), C (2 ml of maggot oil), D (2.5 ml of maggot oil)) on 100 grams of feed. The saline tilapia used was 1.4-1.9 grams/head. The fish were reared for 30 days in 15-liter volume containers, ten fish density, and were fed three times a day. The results showed that fish oil substitution using maggot oil (H. illucens) significantly affected FUE, SGR, absolute weight, FCR, and SR of saline tilapia. The best dose of maggot oil was found in treatment B with a dose of 1.5 ml/100 grams of feed capable of producing FUE (88.783.80%), SGR (7.980.23%/day), absolute weight (41 .17 4.57gram), FCR (1.130.05), and SR (1000.00%).Keywords:BSFBrackish waterSGRProductionWeight